Nano-crystallised carbon-titanium dioxide-bismuth composite photocatalyst for clean water and hydrogen production - Juay, Jermyn (2017)
The use of Titanium Dioxide (Ti02) nanostructures for photocatalytic environmental applications has received significant attention due to a growing emphasis on sustainability. Against this backdrop, this study proposes the use of nano-crystallised carbon composite one-dimensional Ti02 nanostructure with improved photocatalytic activity in the visible light region for such applications. Amongst the studied one-dimensional nanostructures, nanofibrous anatase Ti02 provided a better medium for photocatalytic reactions. Thus a Bb Ti401 t/Ti02 composite nanofiber was assembled through electrospinning. First, it was observed from the experimental results that the formation of the bismuth titanate (B b Ti4011) phase on the anatase Ti02 nanofiber enhanced its photocatalytic performance in the degradation of A07 as well as H2 generation under visible light. The enhanced photocatalytic activity is attributed to the presence of the BbTi4011 which narrowed the band-gap and allowed for improved charge suppression. Moreover, after the formation of the nano-crystallised carbon layer which doped itself into the composite nanofiber, the appearance of the composite nanofiber changed from cream to black. It was observed that there was a significant reduction to the optical band gap which narrowed to 2.55eV (-480nm). Furthermore, through the characterisation study using TEM it demonstrated that the carbon has fully crystallised into the lattice of the composite nanofiber. This indicates that the crystallisation process was a result from the substitution of anions and cations with C-elements into the lattice of the composite nanofiber which triggered the formation of a -2.5nm thick disorder lattice along the fringes. The H2 evolution tests under sacrificial conditions showed that the nano-crystallised carbon composite nanofiber demonstrated excellent ability to generate H2 under visible light irradiation. The introduction of the nano-crystallised carbon dopant not only improved the visible light absorption capability of the composite nanofiber but also created more reaction sites to facilitate the access of reactant. Furthermore it is proposed that the formation of the nano-crystallised carbon layer permitted for an enhanced electrons transfer process through a sequential electron flow. As such, the combination of these factors enriches the photocatalytic performance of the synthesised complex nanofiber. These finding presents the tremendous potential of the complex nanofiber as it is of great importance and promise to utilise solar energy for water purification and energy harvesting applications.